The Effect of Intensive Qur'an Reading Guidance (B2QI) Program on Students’ Qur'an Reading Ability at Ibn Khaldun University Bogor - Putri, Hana Humaira Maulidina Sukmawan; Lisnawati, Santi; Nawawi, M. Kholil (YASIN, 2025)
The ability to read the Qur'an of students in Islamic universities is still a problem. Therefore, Islamic universities have made various efforts to improve the ability to read the Qur'an. One of the efforts made by Ibn Khaldun University Bogor is the launch of the Intensive Qur'an Reading Development / Bina Baca Qur’an Intensif (B2QI) program. This research aims to analyze the effect of the B2QI program on the ability of students on campus to read the Quran. The researchers used a quantitative method with an ex-post facto approach, involving 94 respondents with data collection through questionnaires and tests. The researchers analyzed the results using the Pearson correlation and simultaneous significance tests (F tests). The research results showed that the simultaneous significance test (F test) (171.616> 3.945) with a significance of (0.000 <0.05), then Ho was rejected, and Ha was accepted. It means there is a positive and significant influence between the B2QI program and students' ability to read the Qur'an, with an influence of 65.1%. For this reason, improvements and developments are needed to implement this program so that it can be more beneficial for all students on campus.